Impact of Different Modules of 21-Gene Assay in Early Breast Cancer Patients - Chen, Mengdi; Liu, Deyue; Chen, Weilin; Chen, Weiguo; Shen, Kunwei; Wu, Jiayi; Zhu, Li (Frontiers in Endocrinology, 2021)
Background: The 21-gene assay Recurrence Score (RS) provides additional information on recurrence risk of breast cancer patients and prediction of chemotherapy benefit. Previous studies which examined the contribution of the individual genes and gene modules of RS were conducted mostly in postmenopausal patients. We aimed to evaluate the gene modules of RS in patients of different ages. Methods: A total of 1,078 estrogen receptor (ER)-positive and human epidermal growth factor receptor 2 (HER2)-negative breast cancer patients diagnosed between Jan 2009 and Mar 2017 from Shanghai Jiao Tong University Breast Cancer Data Base were included. All patients were divided into three subgroups: Group A, ≤40y and premenopausal (n=97); Group B, >40y and premenopausal (n=284); Group C, postmenopausal (n=697). The estrogen, proliferation, invasion and HER2 module scores from RS were used to characterize the respective molecular features. Spearman correlation and analysis of the variance tests were conducted for RS and its constituent modules. Results: In patients >40y, RS had a strong negative correlation with its estrogen module (ρ = -0.76 and -0.79 in Group B and C) and a weak positive correlation with its invasion module (ρ = 0.29 and 0.25 in Group B and C). The proliferation module mostly contributed to the variance in young patients (37.3%) while ER module contributed most in old patients (54.1% and 53.4% in Group B and C). In the genetic high-risk (RS >25) group, the proliferation module was the leading driver in all patients (ρ = 0.38, 0.53 and 0.52 in Group A, B and C) while the estrogen module had weaker correlation with RS. The impact of ER module on RS was stronger in clinical low-risk patients while the effect of the proliferation module was stronger in clinical high-risk patients. The association between the RS and estrogen module was weaker among younger patients, especially in genetic low-risk patients. Conclusions: RS was primarily driven by the estrogen module regardless of age, but the proliferation module had a stronger impact on RS in younger patients. The impact of modules varied in patients with different genetic and clinical risks.